2022
DOI: 10.1002/jso.26839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the COVID‐19 pandemic on surgical oncology practice—Results of an SSO survey

Abstract: Background and Objectives: The COVID-19 pandemic significantly affected healthcare delivery, shifting focus away from nonurgent care. The aim of this study was to examine the impact of the pandemic on the practice of surgical oncology.Methods: A web-based survey of questions about changes in practice during the COVID-19 pandemic was approved by the Society of Surgical Oncology (SSO)Research and Executive Committees and sent by SSO to its members.Results: A total of 121 SSO members completed the survey, 77.7% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…These include the use of telemedicine and virtual clinic visits, strategies for which adoption has been hastened by the coronavirus disease 2019 pandemic and are associated with high patient satisfaction and decreased cost without compromising the quality of surgical care 31–34 . Outside of the perioperative period, telemedicine visits may be particularly beneficial in the long-term surveillance of patients undergoing oncologic resection 35,36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the use of telemedicine and virtual clinic visits, strategies for which adoption has been hastened by the coronavirus disease 2019 pandemic and are associated with high patient satisfaction and decreased cost without compromising the quality of surgical care 31–34 . Outside of the perioperative period, telemedicine visits may be particularly beneficial in the long-term surveillance of patients undergoing oncologic resection 35,36 …”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34] Outside of the perioperative period, telemedicine visits may be particularly beneficial in the long-term surveillance of patients undergoing oncologic resection. 35,36 In addition to telemedicine, streamlined access to social workers or case management may provide much-needed resources to those at risk of FT. Social workers may assist patients in understanding the costs associated with their care, facilitate correspondence with payers, assist with obtaining short-term disability or other social services, and identify personnel for discussion within a hospital's billing department. 37 In addition, vouchers for lodging, reimbursement for travel costs, philanthropic funds, and patient advocacy services may be available if social workers are engaged early in the process of caring for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with our demonstration of a trend towards rising urologic surgery volumes with subsequent pandemic waves. Several studies examined the effects of the COVID-19 pandemic in the specialty of urologic oncology surgery and surgical oncology in general [ 8 , 17 ]. Stöss et al [ 5 ] reported an average reduction of 29.3% in oncological resections, as well as reductions in hospital bed and operating room capacities throughout Europe.…”
Section: Discussionmentioning
confidence: 99%